Implementation of the Investigation Process Against Perpetrators of Illegal Logging in the Rembang Police Resort Area - Saputro, Noor Wachied Eko; Arpangi, Arpangi (Jurnal Hukum Khaira Ummah, 2025)
Environmental management provides economic, social and cultural benefits and needs to be carried out based on the principles of caution, environmental democracy, decentralization, as well as recognition and appreciation of local wisdom and environmental wisdom, so that the Indonesian environment must be protected and managed properly based on the principles of state responsibility, the principle of sustainability and the principle of justice. The purpose of this research is to find out and analyze the implementation of the investigation process against perpetrators of illegal logging in the Rembang Police Resort area. To find out and analyze the obstacles and solutions in the implementation of the investigation process against perpetrators of illegal logging in the Rembang Police Resort area. The method used by the researcher is sociological legal approach And The specifications in this study include analytical descriptive. The sources and types of data in this study are primary data obtained through interviews. And Secondary data was obtained from literature studies. Data was analyzed qualitatively. using the theory of the rule of law and the theory of the legal system. Based on the results of the research that The implementation of the investigation process for perpetrators of illegal logging in the jurisdiction of the Rembang Police Resort involves various stages regulated in criminal procedure law. Investigators, who are generally members of the Police, will conduct an initial investigation based on reports, complaints, or arrests caught red-handed. The investigation process then involves examining witnesses, suspects, securing evidence, and compiling case files to be submitted to the prosecutor. Obstacles in the implementation of the investigation process for perpetrators of illegal logging in the Rembang Police Resort area include the availability of data and evidence, coordination between agencies, and suboptimal law enforcement. The solution includes improving data quality, harmonizing regulations, increasing the capacity of law enforcement officers, and involving the community in efforts to prevent and eradicate forest destruction.